Pola Kendali Komunikatif Pembina Dalam Meningkatkan Kepatuhan Aturan Mahasiswa Ma’had Al Jamiah IAIN Parepare - Nurbatin; Nurhakki; A.Dian Fitriana (Journal of Media and Communication Studies, 2023)
Communication patterns are ways of conveying messages from a communicator to communicants directly or by using tools and facilities as media. The purpose of this research is to find out the communication patterns of coaches in increasing compliance with Ma'had Al Jamiah IAIN Parepare students. This research use desciptive qualitative approach. using observation, interview and documentation data collection techniques, the informants were students and supervisors of the Ma'had Al Jamiah IAIN Parepare hostel . The results of the research included; (1) The description of student compliance shows non-compliance with programs/activities carried out by the dormitory, the form of student disobedience is not participating in learning activities optimally including not depositing Arabic and English memorization and not participating in learning programs. (2) The communication patterns used by the coach are group communication patterns using a lecture and advice approach to students of Ma'had Al-Jamiah IAIN Parepare, communication techniques like this are very important, and are able to change the mindset of students from previously only taking regulations lightly to being more understand the rules themselves. (3) Obstacles that affect student compliance, namely; obstacles due to the busyness of the campus where students do not take part in learning on the grounds of being busy outside the dormitory, and the self-awareness factor, namely self-awareness determines great motivation and willingness for students to be present in student dormitory program activities.